2020
DOI: 10.22146/mot.55176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozonated Olive Oil in Topical Application towards Osteoblast Number and Angiogenesis of Alveolar Bone in Periodontitis Healing Process (in vivo study in Sprague dawley Rats)

Abstract: Ozonated olive oil has been widely used as a local infection therapy to overcome bacterial resistance from antibiotics with systemic administration. However, the disadvantage of systemic antibiotics is it cannot be used in large doses for local infection therapy. Periodontitis is an infectious disease that causes alveolar bone damage. In the periodontitis healing process, osteoblasts and angiogenesis play essential roles in bone regeneration. The study aims to determine the effect of topical application ozonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 14 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The results of the study demonstrated that osteoblasts number increased from day 3, 5, 7, and continued up to day 14 both in ozonated olive oil treatment and placebo group, which indicated by the observation time that affected the number of osteoblasts significantly. The number of blood vessels peaked on day 7 decreased up to day 14, both in the treatment and the placebo group (Herawati et al, 2020). The collagen density continued up to day 14, the pattern like to osteoblast.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The results of the study demonstrated that osteoblasts number increased from day 3, 5, 7, and continued up to day 14 both in ozonated olive oil treatment and placebo group, which indicated by the observation time that affected the number of osteoblasts significantly. The number of blood vessels peaked on day 7 decreased up to day 14, both in the treatment and the placebo group (Herawati et al, 2020). The collagen density continued up to day 14, the pattern like to osteoblast.…”
Section: Resultsmentioning
confidence: 90%
“…Rats were injected with ketamine hydrochloride (0.2 mL/ 200 g body weight) intramuscular in the upper thigh to give a sedative effect before induced periodontitis by placing silkligature around sub-mandibular incisors. Tissues inflammation was curetted after 7 days inducing periodontitis, ozonated olive oil (PurO3 LLC, Fayetteville, AR USA) was applied to treatment groups and 1% Sodium Carboxymethylcellulose (CMC-Na) was applied to placebo groups, twice a day to mandible incisors periodontal pocket using explorer tip (Herawati et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observation on day 7 due to the initiation of new bone formation to synthesize and secrete matrix, and day 14 was the peak of the osteoblasts activity after bone loss. The peak of osteoblast cell activity would lead to increased collagen and matrix deposition by osteoblasts [15]. This study aimed to analyze the number of osteoblasts, osteoclasts and the expression of bone morphogenetic protein-2 in alveolar periodontitis rats at day 7 and 14 after administering the extract gel of cocoa pod husk (Theobroma cacao L.).…”
Section: Introductionmentioning
confidence: 99%